2023
DOI: 10.1111/sltb.12980
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal thoughts and behaviors in youth seeking mental health treatment in Texas: Youth Depression and Suicide Network research registry

Beth D. Kennard,
Jennifer L. Hughes,
Abu Minhajuddin
et al.

Abstract: IntroductionSuicidality in youth is a serious public health problem. The Texas Youth Depression and Suicide Research Network (TX‐YDSRN) was initiated in 2020 to create a research registry for youth with depression and/or suicidality in Texas. This report presents baseline clinical/demographic characteristics of the first 1000 participants, focusing on suicidal thoughts and behaviors.MethodsThe registry includes 8–20‐year‐old youth receiving treatment for depression, or who screen positive for depression and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…In 2021, 9.3% of children aged 3-17 in Texas received mental healthcare in the past year, compared to 11.2% of children in the United States [5] A study utilizing baseline data on 1000 participants identified that 79.6% of the sample had a primary depressive disorder, with nearly half reporting one or more lifetime suicide attempts and 90% reporting lifetime or current suicidal ideation [6]. The same study found Psych 2024, 6 that participants with past or current suicidality had greater illness severity in depression, anxiety, and suicidal thoughts or behaviors, lower resilience, and higher rates of trauma exposure than those without suicidality. The limited number of mental health clinicians available heightens widespread mental health struggles when considering how essential clinicians are to providing treatment for suicidal youth patients.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, 9.3% of children aged 3-17 in Texas received mental healthcare in the past year, compared to 11.2% of children in the United States [5] A study utilizing baseline data on 1000 participants identified that 79.6% of the sample had a primary depressive disorder, with nearly half reporting one or more lifetime suicide attempts and 90% reporting lifetime or current suicidal ideation [6]. The same study found Psych 2024, 6 that participants with past or current suicidality had greater illness severity in depression, anxiety, and suicidal thoughts or behaviors, lower resilience, and higher rates of trauma exposure than those without suicidality. The limited number of mental health clinicians available heightens widespread mental health struggles when considering how essential clinicians are to providing treatment for suicidal youth patients.…”
Section: Introductionmentioning
confidence: 99%